THE INFLUENCE OF THE WORLD OF K-POPERS ON LIFESTYLE OF STUDENTS OF UIN RADEN FATAH PALEMBANG - Yudi Latama; Zinta Sari, Adela; Sinar Saprini; Dwie Asbania; Lidia; Pipit Kun Maya; Ayi S. Ruqayyah; Na’ilah Imtitsal Lathifah; Adelia Apriliana Bella; Jevi Saputra (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2022)
The K-Pop world is now starting to go global, many groups of teenagers admire the artist who lives in the country of ginseng. The purpose of this study is to find out how K-Pop influences the lifestyle of teenagers in college students such as how to dress, buying idol goods, and so on, besides that it is also to find out how the impact is getting from the K-Pop world. This research method is a quantitative research with a pretest-posttest design. The subjects of this study were determined using a simple random sampling technique, in which the sample was 30 students of UIN Raden Fatah Palembang. The data were analyzed using the SPSS test with the Paired Sample Test technique where the value of Sig (2-tailed) was 0.023 0.05. The results showed that there was a significant influence between the world of K-Pop and the lifestyle of college students. Thus, it can be concluded that the K-Pop world influences the lifestyle of Raden Fatah State Islamic University students from the results of the Pre-Test and Post-Test of the experimental group, before and after being given treatment in the form of watching the music video "Make A Wish" by NCT ​​U